Techniques of Differentiation - Exercise 3

Exercise 3. Solve the equation $\displaystyle \frac{dy}{dx}
= 0$ when

\begin{displaymath}y = \frac{x^2 - x + 5}{2x+3}\end{displaymath}

Answer. First we need to find the derivative of y. This will be done via the quotient rule. We have

\begin{displaymath}\frac{dy}{dx} = \frac{(2x-1)(2x+3)- 2(x^2-x+5)}{(2x+3)^2} =
\frac{2x^2 + 6x -13}{(2x+3)^2} \;\cdot\end{displaymath}

So to have $\displaystyle \frac{dy}{dx}
= 0$, we should have

\begin{displaymath}2x^2 + 6x -13 = 0\;.\end{displaymath}

This is a quadratic equation. The quadratic formulas give

\begin{displaymath}x_1 = \frac{-3 + \sqrt{35}}{2}\;\; \mbox{or}\;\;x_2 = \frac{-3 - \sqrt{35}}{2}\end{displaymath}

which are the two solutions to the equation $\displaystyle \frac{dy}{dx}
= 0$.

[Back] [Next]
[Trigonometry] [Calculus]
[Geometry] [Algebra] [Differential Equations]
[Complex Variables] [Matrix Algebra]

S.O.S MATHematics home page

Do you need more help? Please post your question on our S.O.S. Mathematics CyberBoard.

Mohamed A. Khamsi

Copyright 1999-2018 MathMedics, LLC. All rights reserved.
Contact us
Math Medics, LLC. - P.O. Box 12395 - El Paso TX 79913 - USA
users online during the last hour